2012
DOI: 10.1002/ana.23698
|View full text |Cite
|
Sign up to set email alerts
|

Central role and mechanisms of β‐cell dysfunction and death in friedreich ataxia–associated diabetes

Abstract: Objective Friedreich ataxia (FRDA) is an autosomal recessive neurodegenerative disease caused in almost all cases by homozygosity for a GAA trinucleotide repeat expansion in the frataxin gene. Frataxin is a mitochondrial protein involved in iron homeostasis. FRDA patients have a high prevalence of diabetes, the pathogenesis of which is not known. We aimed to evaluate the relative contribution of insulin resistance and β-cell failure and the pathogenic mechanisms involved in FRDA diabetes. Methods Forty-one F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 59 publications
(77 reference statements)
3
94
1
4
Order By: Relevance
“…It is plausible that the mitochondrial dysfunction that occurs in FA makes DM apparent at younger ages than in the general population 37. Aging is also accompanied by changes in body composition that may hasten onset of DM (increased fat mass, particularly visceral), and individuals with FA may also demonstrate these changes at comparatively younger ages 38. It has also been previously reported that the presence of a point mutation in the frataxin gene also is associated with increased likelihood of DM,39 although we did not detect a statistically significant association in this analysis.…”
Section: Discussioncontrasting
confidence: 70%
“…It is plausible that the mitochondrial dysfunction that occurs in FA makes DM apparent at younger ages than in the general population 37. Aging is also accompanied by changes in body composition that may hasten onset of DM (increased fat mass, particularly visceral), and individuals with FA may also demonstrate these changes at comparatively younger ages 38. It has also been previously reported that the presence of a point mutation in the frataxin gene also is associated with increased likelihood of DM,39 although we did not detect a statistically significant association in this analysis.…”
Section: Discussioncontrasting
confidence: 70%
“…Human and rat b-cells were transfected with 30 nmol/L small interfering RNA (siRNA) and lipofectamine RNAiMAX (Invitrogen) diluted in Opti-MEM I (Invitrogen) as described (43), resulting in a transfection efficiency of .90% (43,44). After overnight transfection, the cells were cultured for 48 h before further use.…”
Section: Rna Interferencementioning
confidence: 99%
“…Specifically, glucagon-like peptide 1 (GLP-1) and forskolin were found to reduce cell death, normalize free radical production and increase frataxin by 1.5–2 fold [37]. In a similar study of β-cells, analogs of GLP-1 and glucose-dependent insulinotropic polypeptide (GIP) have been found in vitro to partially protect frataxin-deficient islet cells from apoptosis [38]. These compounds have not yet been tested in human FRDA patients.…”
Section: Treatment Of Frda: Medicationsmentioning
confidence: 99%